Cognitive, Emotional, and Auto-Activation Dimensions of Apathy in Parkinson's Disease - Del-Monte, Jonathan; Bayard, Sophie; Graziani, Pierluigi; Gély-Nargeot, Marie C. (Frontiers in Behavioral Neuroscience, 2017)
Apathy is one of the most frequent non-motor manifestations of Parkinson’s disease (PD) and can lead to a range of deleterious outcomes. In 2006, Levy and Dubois proposed a model that distinguishes three different apathy aetiologies in PD divided into three subtypes of disrupted processing: ‘emotional-affective’, ‘cognitive’ and ‘auto-activation’. These three dimensions, associated with dopamine depletion caused by the pathology, would lead to the emergence of apathy in PD. The aim of this mini review was to describe and discuss studies that have explored links between apathy and the three subtypes of disrupted processing proposed by Levy and Dubois (2006), as well as the links between these dimensions and dopamine depletion in Parkinson's disease. The lack of consensus regarding the emotional-affective correlates of apathy and the lack of evidence supporting the auto-activation deficit hypothesis, do not clearly confirm the validity of Levy and Dubois’ model. Furthermore, the suggested association between dopaminergic depletion and apathy must also be clarified.